Heart failure and diabetes mellitus: insight into comorbidity - Nina A. Petunina (Endocrinology Research Centre, 2019)
Diabetes mellitus (DM) and heart failure (HF) are frequent comorbidities with a bidirectional relationship. Patients with HF have increased risk of developing DM, and those with DM are at greater risk of developing HF. HF does not fit clearly into the microangiopathy and macroangiopathy groups. It is known that coronary artery disease and arterial hypertension are the major causes of HF; however, it has been shown that DM can trigger functional and structural abnormalities in the myocardium via diabetic cardiomyopathy, a condition with either restrictive or dilated phenotype. While HF treatment is equally effective and safe in patients with and without DM, this statement is not applicable for antidiabetic treatment. Several antidiabetic drugs, such as rosiglitazone, pioglitazone and saxagliptin increase the risk of hospitalisation for HF, therefore these antidiabetic drugs are contraindicated in patients with DM and HF or patients at risk of developing HF. Despite a large number of clinical evidence, uncertainty about the safety of antidiabetic drugs in patients with HF always exists. In this review, the issues of DM treatment in patients with HF are addressed in detail.